How much does decompressive laparotomy reduce the mortality rate in primary abdominal compartment syndrome?: A single-center prospective study on 66 patients. Issue 5 (February 2017) - Muresan, Mircea; Muresan, Simona; Brinzaniuc, Klara; Voidazan, Septimiu; Sala, Daniela; Jimborean, Ovidiu; Hussam, Al Husseim; Bara, Tivadar; Popescu, Gabriel; Borz, Cristian; Neagoe, Radu
Abstract : Abstract: Contribution of decompressive laparotomy within the framework of the complex therapeutic algorithm of abdominal compartment syndrome (ACS) is cited with an extremely heterogeneous percentage in terms of survival. The purpose of this study was to present new data regarding contribution of each therapeutic step toward decreasing the mortality of this syndrome. This is a longitudinal prospective study including 134 patients with risk factors for ACS. The intra-abdominal pressure was measured every hour indirectly based on transvesical approach and the appearance of organ dysfunction. Specific therapy for ACS was based on the 2013 World Society of Abdominal Compartment Syndrome guidelines, which include laparotomy decompression. Management of the temporarily open abdomen included an assisted vacuum wound therapy. Of 134 patients, 66 developed ACS. The average intra-abdominal pressure significantly decreased after therapy and decompression surgery. The overall rate of mortality was 27.3% with statistical significance in necrotizing infected pancreatitis. Surgical decompression performed within the first 24 hours after the onset of ACS had a protective role against mortality (odds ratio <1). The average time after which laparotomy decompression was performed was 16.23 hours. The complications occurred during TAC were 2 wound suppurations and 1 intestinal obstruction. Wound suppurations evolved favorably by using vacuum wound-assisted therapy associated with the general treatment, whereas for occlusion, resurgery was performed after which adhesions dissolved. The final closure of the abdomen was performed at a mean of 11.7 days (min. = 9, max. = 14). The closure type was primary suture of the musculoaponeurotic edges in 4 cases, and the use of dual mesh in the other 11 cases. The highest mortality rate in the study group was registered in patients with necrotizing pancreatitis and the lowest in trauma group. Surgical decompression within the framework of the complex algorithm treatment of ACS contributed to the reduction of mortality by 8.7%. It is extremely important that the elapsed time since the initiation of the ACS until the surgical decompression is minimal (under 24 hours).